2015
DOI: 10.1007/s12035-015-9327-7
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats

Abstract: Autophagy occurs prior to apoptosis and plays an important role in cell death regulation during spinal cord injury (SCI). This study aimed to determine the effects and potential mechanism of the glucagon-like peptide-1 (GLP-1) agonist extendin-4 (Ex-4) in SCI. Seventy-two male Sprague Dawley rats were randomly assigned to sham, SCI, 2.5 μg Ex-4, and 10 μg Ex-4 groups. To induce SCI, a 10-g iron rod was dropped from a 20-mm height to the spinal cord surface. Ex-4 was administered via intraperitoneal injection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…Accumulating evidence indicates that autophagy is activated in various animal models of the central nervous system, such as traumatic brain and spinal cord injury (Park et al, 2015;Li et al, 2015a), cerebral and spinal cord ischemia (Villamil-Ortiz and CardonaGomez, 2015;Li et al, 2015b), intracerebral hemorrhage (Yang et al, 2015), and neurodegeneration (Navone et al, 2015). In the model of cerebral ischemia, activated autophagy occured in different cell types such as neurons , astrocytes (Qin et al, 2010) and vascular endothelial cells (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that autophagy is activated in various animal models of the central nervous system, such as traumatic brain and spinal cord injury (Park et al, 2015;Li et al, 2015a), cerebral and spinal cord ischemia (Villamil-Ortiz and CardonaGomez, 2015;Li et al, 2015b), intracerebral hemorrhage (Yang et al, 2015), and neurodegeneration (Navone et al, 2015). In the model of cerebral ischemia, activated autophagy occured in different cell types such as neurons , astrocytes (Qin et al, 2010) and vascular endothelial cells (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an intracellular catabolic mechanism that maintains a balance between protein synthesis and degradation, which can both promote cell survival and induce cell death (autophagic cell death) depending on the specific pathological event. Accumulating evidence has demonstrated that autophagy activation is elevated in the central nervous system under stressed conditions (Park et al, 2015;Li et al, 2015a;Villamil-Ortiz and Cardona-Gomez, 2015;Yang et al, 2015). As shown in the previous studies, autophagy plays an important role in spinal cord injury (Baba et al, 2009;Seo et al, 2015;Fujita et al, 2015); however, its expression change and mechanism after spinal cord I/R injury are largely unknown.…”
Section: Introductionmentioning
confidence: 86%
“…SCI negatively affects a patient's quality of life and causes significant economic burden to society. Significant efforts have been made to search for new drug candidates that will promote functional recovery after SCI (Li et al, ; Zhang et al, ). In our study, systemic administration of melatonin immediately after SCI in female rats reduced spinal cavity volume and improved functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistently acceptable that dropping a 10 g weight from the height of 25 mm induced a severe degree of SCI in the rat model [49], which is commonly used in the autophagic study of spinal cord contusion [32,50,51,52,53]. Using this severe contusion injury model, past studies showed that autophagy was present at higher levels when compared to the non-injured case at single time points after SCI, namely, at day 1 [54], day 3 [44,55], day 4 [56], and day 7 [57] after injury. However, the temporal pattern analysis that reveals changes in autophagic activity over time were not investigated in these studies.…”
Section: Temporal Pattern Of Autophagic Activation In Scimentioning
confidence: 99%
“…In contusion injury, the therapeutic agents of atorvastatin and simvastatin (two inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase) [53,98], metformin [100], exendin-4 (an agonist of glucagon-like peptide-1) [55] and vitamins C and E (antioxidants) [57], worked through the mechanisms of apoptosis inhibition, combined with upregulation of autophagy after SCI. However, methylprednisolone (a synthetic glucocorticoid hormone), valproic acid (a histone deacetylase (HDA) inhibitor) and systemic bisperoxovanadium (a small-molecule protein tyrosine phosphatase (PTP) inhibitor) also have effects of downregulating the level of autophagy in the treatment of contusion injury [47,54,99].…”
Section: Pharmacological Intervention Of Autophagy In Scimentioning
confidence: 99%